Identification of markers for functional traits in Murrah buffaloes - SHARMA, UPASNA; BANERJEE, PRIYANKA; JOSHI, JYOTI; KAPOOR, PRERNA; RAHEJA, MEENAL; VIJH, RAMESH KUMAR (The Indian Journal of Animal Sciences, 2021)
Twelve half sib families were created and two functional traits, viz. age at first heat and age at first calving were recorded for 4,851 and 946 daughters belonging to 12 sires. Partial genome scan was carried out using Interval Mapping with different algorithms. The QTLs obtained for each half sib family were further subjected to meta analysis to identify chromosomal regions associated with age at first heat and age at first calving on 8 chromosomes of buffalo. We identified 4 metaQTL regions on chromosomes BBU1q, BBU6, BBU7, BBU8 and BBU10; 3 metaQTL regions on BBU2q; 2 metaQTL regions on BBU9 and one on BBU15 of buffalo. Comparative genomics was used for finding out genes underlying the meta-QTL regions. 1019 genes were found to be underlying the metaQTL regions in buffaloes assuming buffalo-cattle-human synteny. Several of these genes are supposedly important candidate genes for further analysis as several of them revealed functions related to fertility. The QTL markers identified in the present analysis can be used in the breeding programs of buffalo to select the bulls which affect the functional traits and thus reduce the cost of production.